Utilization of Film Copyright Through Digital Applications in Modifying Original Works: A Study of Film Novel Adaptations - Ike Yulita; Akhmad Fadlan; Nurul Iza Ananda; Dudung Hidayat; Irma Maulida (PT FORMOSA CENDEKIA GLOBAL, 2025)
The advancement of digital technology has transformed the creation and consumption of intellectual works. Digital applications facilitate the swift modification and adaption of original works, creating new potential but also presenting intricate legal challenges, especially concerning copyright. Original creations, whether music, photographs, films, or software, can be readily altered, amalgamated, and disseminated via diverse digital media. Legal certainty between the creator or copyright holder and an existing work affords comprehensive protection to the copyright owner. For instance, in derivative works, if an individual transforms a written novel into a film, they must adhere to the protocols set forth in the 2002 Copyright Law. This research employs the Normative Juridical methodology. The normative legal research method involves the examination of both written and unwritten positive laws. This is conducted through the examination of literary sources or secondary data. This research seeks to elucidate the constraints involved in converting an original work into a derivative work that retains copyright protection, while also examining the necessity of issuing licenses as a legal safeguard in the adaptation process, especially from novels to films in the digital age.